Information systems development methodologies, techniques and tools - Avison, D.E (McGraw-Hill, 2006)
Covers Information Systems Development Context, the Systems Development Lifecycle, Themes of Systems Development, Techniques, Methodologies, Tools and Toolsets and Issues and Frameworks. This title analyzes context, issues and real-world problems associated with information systems development.